Development of Web-based Geographic Information System for Water Quality Monitoring of Watershed in Malang - Rosyida, Novita; Dinira, Layta; Rusydi, Alfi Nur; Saputra, Agung Dwi; Setiabudi, Ginanjar (Universitas Nusantara PGRI Kediri, 2022)
Human activity and climate change significantly impact water quality, especially in Malang's watershed. This research aims to develop a web-based Geographic Information System (Web- GIS) for water quality monitoring in that watershed. The water quality data had been collected from Enviromental Office of Malang District and Malang City. Water quality in this application was determined using the STORET method, comparing water quality data to water quality standards according to Government regulation so that the water quality status at each monitoring point will be known. The total 57 monitoring points are visualized spatially in this application based on the sampling location plotted by Global Positioning System (GPS). The longitude and latitude coordinates of the monitoring location had been converted in GeoJSON using Quantum GIS (QGIS) software. Google Map API key was used to display a sampling location map on the website. Web-GIS application was tested functionally using a black box, compatibility, and usability testing. Based on the testing results, it worked correctly on Chrome, Edge, Mozilla, and Opera browsers for PC/Laptops and also for browsers on Android smartphones version 4 and above. The application could be appropriately used and efficiently based on usability testing results.